Answer:
C
Step-by-step explanation:
since we're being told to convert the ratio to fraction then it is C. note that 4 ratio is also the same as dividing 4 by 6
Rewrite g(x) as x-1
------
4
and then substitute this result for x in f(x) = x^2 - 3x + 3:
f(g(x)) = (x-1)^2 / 4^2 - 3(x-1)/4 + 3.
At this point we can substitute the value 5 for x:
f(g(5)) = (5-1)^2 / 4^2 - 3(5-1)/4 + 3
= 16/16 - 3(4/4) + 3 = 1 - 3 + 3 = 1
Therefore, f(g(5)) = 1.
Answer:
two to the five sixths power
Step-by-step explanation:
![\sqrt{2} *\sqrt[3]{2} =2^{\frac{1}{2} }*2^{\frac{1}{3} } = 2^{\frac{1}{2} +\frac{1}{3}}=\\=2^{\frac{5}{6} }](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D%20%2A%5Csqrt%5B3%5D%7B2%7D%20%3D2%5E%7B%5Cfrac%7B1%7D%7B2%7D%20%7D%2A2%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%3D%202%5E%7B%5Cfrac%7B1%7D%7B2%7D%20%2B%5Cfrac%7B1%7D%7B3%7D%7D%3D%5C%5C%3D2%5E%7B%5Cfrac%7B5%7D%7B6%7D%20%7D)